Efficiency, market structure and performance of the insurance industry in an emerging economy - Kenneth Ofori-Boateng; Williams Ohemeng; Ernest Ahawaadong Boro; Elvis Kwame Agyapong (Cogent Economics & Finance)
This paper investigated the structure of the market, efficiency and performance (profitability) of the general insurance industry in the Ghanaian economy. The overriding objective was to evaluate the impact that regulatory informed market structure would have on the pricing behaviour; examining the hypothesis of the Structure Conduct Performance (SCP) for the general insurance market. Using data comprising a panel of 29 general insurance firms from 2008–2019, the paper used the Herfindahl Hirschman Index and the concentration ratio to measure the SCP in addition to computing efficiency as a measure for the Efficient Structure (ES) hypothesis. Using a Panel Corrected Standard Error and settling on Random Effect techniques, the paper found no evidence to suggest collusive firm behaviour among general insurers. The findings therefore supported the ES hypothesis, and rejected the SCP hypothesis. The paper presents insight into understanding the behaviour of insurance companies in the new markets inspired by regulation.